Generation of Human Oogonia From Induced Pluripotent Stem Cells In Vitro. Issue 3 (March 2019) - Yamashiro, Chika; Sasaki, Kotaro; Yabuta, Yukihiro; Kojima, Yoji; Nakamura, Tomonori; Okamoto, Ikuhiro; Yokobayashi, Shihori; Murase, Yusuke; Ishikura, Yukiko; Shirane, Kenjiro; Sasaki, Hiroyuki; Yamamoto, Takuya; et al.
Abstract : (Abstracted from Science 2018;362:356–360) Studies have shown that mouse pluripotent stem cells (PSCs) can be induced into primordial germ cell–like cells (hPGCLCs), which, following transplantation under appropriate conditions, can contribute to the development of gametes capable of developing into fertile offspring. Human in vitro gametogenesis from PSCs has long-reaching implications in reproductive medicine but has not yet been achieved.